Model Kontrol Manajemen Laktasi di UPT Puskesmas Pahandut Kota Palangkaraya - Fitriani Ningsih; Rizki Muji Lestari; Raynaldi Raynaldi (Jurnal Surya Medika (JSM), 2021)
In breastfeeding, it is necessary to carry out lactation management efforts by the mother to support the success of exclusive breastfeeding, because in essence lactation management starts during pregnancy, after childbirth, and during the breastfeeding period of the baby. Lactation management regulates the entire breastfeeding process to run smoothly and successfully, from the production of breast milk to the process of the baby sucking and swallowing breast milk. Therefore, it is necessary to support the fulfillment of breastfeeding for infants, namely the control model of lactation management which aims to ensure that lactation management can be carried out properly so that exclusive breastfeeding can be carried out. The design of this study used a Quasy Experiment research design with a Pre-Post-test Control Group Design, using a sample of 30 post-partum mothers in Pahandut Health Center, Palangka Raya City. This group was divided into 15 respondents as the intervention group and 15 respondents as the control group. In this study using the Paired T-Test statistical test. The results of statistical tests were also obtained from each control variable, the value of P value for counseling (0.000), family support (0.000), exclusive breastfeeding policy (0.000), breast care (0.017) and hypno breastfeeding (0.048). P value <of a (0.05) means that the variable of counseling, family support, exclusive breastfeeding policy, breast care and hypno breastfeeding are very effective in helping increase milk production.